Correlation analysis of serum FGF9, Sestrin 2 and HBDH with the severity of sepsis: Serum FGF9, Sestrin 2 and HBDH with the severity of sepsis - He, Jian; Lin, Xinru; Ding, Xiang; Liu, Maoxia (Journal of Medical Biochemistry, 2025)
Objective: To explore the correlation between serum fibroblast growth factor 9(FGF9), Sestrin2 and hydroxybutyrate dehydrogenase (HBDH) and the severity of sepsis, and to analyze the predictive value of FGF9, Sestrin2 and HBDH for clinical outcome. Methods: A retrospective examination of 125 patients with sepsis admitted to our institution between May 2022 and May 2025 was carried out. According to the severity of the disease, There were 50 cases in the septic shock group and 75 cases in the sepsis group. According to the clinical outcomes of the patients, they were divided into a death group of 103 cases and a survival group of 22 cases. Observe the levels of serum FGF9, Sestrin2 and HBDH in each group. Analysis of the relationships between FGF9, Sestrin2, HBDH, and the severity of sepsis was done using the Spearman correlation coefficient model. Using multivariate logistic regression analysis, the factors influencing the prognosis of patients with sepsis were investigated. FGF9, Sestrin2, and HBDH were evaluated for their prognostic usefulness for the prognosis of sepsis patients using the receiver operating characteristic (ROC) curve. Results: Compared with the sepsis group, The level of FGF9 in the septic shock group was lower [(122.41±21.45) pg/mL vs (145.36±23.68) pg/mL], while the levels of Sestrin2 and HBDH were both higher [(15.75±2.34) ng/mL] vs (8.36 + 0.93) ng/mL, (232.14-34.77) U/L vs (166.25 + 24.85) U/L], the differences were statistically significant (P<0.05). Compared with the survival group, The level of FGF9 in the death group was lower [(112.05±20.61) pg/mL vs (133.25±22.14) pg/mL], while the levels of Sestrin2 and HBDH were both higher [(19.25±2.85)ng/mL] vs (12.42 + 2.33) ng/mL, (261.25-37.25) U/L vs (204.25 + 32.18) U/L]. Spearman correlation coefficient analysis showed that FGF9 was negatively correlated with the severity of sepsis (P<0.05), whereas the degree of sepsis was positively connected with both Sestrin2 and HBDH (P<0.05). Sequential Organ Failure Assessment (SOFA), Acute Physiology and Chronic Health Evaluation II (APACHE II), procalcitonin, FGF9, Sestrin2, and HBDH are risk factors that impact the prognosis of sepsis patients, according to multivariate logistics regression analysis (P<0.05). The results of ROC curve analysis showed that the combined detection of FGF9, Sestrin2 and HBDH had a better predictive effect on the prognosis of patients with sepsis (P<0.05). Conclusion: The amount of FGF9 in septic shock patients is comparatively low, while the levels of Sestrin2 and HBDH are relatively high. As the severity of the disease increases, the level of FGF9 gradually decreases, while the levels of Sestrin2 and HBDH gradually increase, which have a certain correlation with the severity of the disease. The prognosis of sepsis patients can be ascertained by measuring the levels of FGF9, Sestrin2, and HBDH.